Empirical models for the structure-borne sound power input from artificial and natural rainfall. (May 2020) - Yu, Y.; Hopkins, C.
Highlights: Empirical models developed to predict rain noise in buildings and cars. Models developed for artificial rainfall up to terminal velocity. Models developed for natural rainfall at terminal velocity. Models allow for inclined plates and surface water on the plate. Conversion factors between artificial and natural rainfall. Abstract: Interpretation and application of laboratory rain noise measurements using artificial rain on roof elements of buildings and cars requires validated prediction models for the structure-borne sound power input during artificial and natural rainfall. Empirical models have therefore been developed for the time-dependent force on horizontal and inclined plates with artificial and natural rainfall. For inclined plates, two approaches have been developed. The first approach uses the empirical model for a horizontal plate (dry or with surface water) and converts it to an inclined plate by estimating the drop velocity in the direction perpendicular to the plate surface. The second approach extends a semi-empirical model for dry, horizontal plates so that it applies to drops falling at terminal velocity onto dry, inclined plates. Experimental work was carried out to validate these models. Measurements for single 4.5 mm drops impacting on plates inclined up to 60° showed better agreement with the second approach. Artificial rain measurements for rainfall rates between 24 and 30 mm/h confirmed the validity of this second approach even though it assumes a dry surface. However, for heavy and torrential rain (i.e. rainfall rates higher than 40 mm/h), the first approach to modelling allows the option to include a 1 or 2 mm water layer on the surface. The validated model for the second approach has been used to calculate conversion factors between laboratory measurements with artificial rain to other situations with natural or artificial rainfall, and between measurements on roof elements that are inclined at different angles.